2021
DOI: 10.1021/acssuschemeng.0c06808
|View full text |Cite
|
Sign up to set email alerts
|

Few Layer Graphene/TiO2 Composites for Enhanced Solar-Driven H2 Production from Methanol

Abstract: Here is presented the elaboration of Few Layer Graphene/TiO 2 photocatalytic composites (FLG/TiO 2 ) with FLG loadings from 0.5 to 11 wt.%. Contrary to commonly used (reduced) graphene oxide obtained by long and harsh conditions synthesis, FLG was synthesized by simple, fast, efficient and eco-friendly exfoliation method. The enhancement of defective/functionalized sites density for attachment of TiO 2 species was achieved via calcination process at 450 °C. The nanocomposites were evaluated toward H 2 producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 63 publications
(150 reference statements)
1
17
0
Order By: Relevance
“…The fact that the charge transfer in the present composites occurs is somehow confirmed earlier via enhanced photocatalytic activity and in general, it is well established in this type of hybrids [9,10].…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…The fact that the charge transfer in the present composites occurs is somehow confirmed earlier via enhanced photocatalytic activity and in general, it is well established in this type of hybrids [9,10].…”
Section: Resultssupporting
confidence: 84%
“…The synthesis of FLG, FLG', TiO2 and their composites were detailed previously [10,18,19]. In brief, FLG and FLG' were obtained via exfoliation of expanded graphite in water in the presence of bio-surfactant (bovine serum albumin) with help of mixing-assisted sonication.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As an increasingly mature application, nuclear power technology can even completely replace fossil fuels to meet future energy needs. However, a large amount of nuclear wastewater will be generated during the nuclear fuel cycle process, including nuclear facility decommissioning, equipment maintenance, accident treatment, etc. , Researchers have developed various methods to remove or extract uranium ions in wastewater. Unfortunately, this type of wastewater contains not only radioactive elements but also various organic substances, including alkyl glycosides, xanthan gum, oxalic acid, citric acid, and tannic acid (TA) . In addition, the industrial electroplating wastewater was also found to contain TA .…”
Section: Introductionmentioning
confidence: 99%
“…[61] The latter is the 002 diffraction plane, characteristic for graphitic materials. [22,44,62] A qualitative study of the crystal size and dspace was performed to further exploit XRD data by understanding of the atomic layer disposition on the C3N4 in-plane. Considering that the studied materials are heterogeneous, supported by SEM, this analysis is valid knowing that XRD is an average measurement of the heptazine unit repetition.…”
Section: Physicochemical Characterizationmentioning
confidence: 99%